ROLE OF JAMMU AND KASHMIR WOMEN’S DEVELOPMENT CORPORATION TOWARDS THE UPLIFTMENT OF WOMEN: - A SOCIOLOGICAL STUDY IN THREE DISTRICTS OF KASHMIR VALLEY. (CAHIERS MAGELLANES-NS, 2024)
Men and women have never been accorded equal treatment or social standing in human history.  similar to how society in Jammu and Kashmir is.  Despite their desire for equality, women have not been able to live lives that are perfectly comparable to those of men.  Compared to later eras, women's status in ancient India was far more favorable.   Throughout the Middle Ages, women were almost forced into servitude; but, following independence and under the British Empire, their status continued to improve. Indian women are practically given the same status as men these days. Their disabilities in terms of politics, economy, education, and other areas have all been lawfully eliminated. In addition to these initiatives, the Indian government founded a women's development corporation  at the national level and The programs offered by this corporation to close the gender gap in Jammu and Kashmir are the main topic of this paper.